2017
DOI: 10.1080/17470919.2017.1304990
|View full text |Cite
|
Sign up to set email alerts
|

Facial affect processing in social anxiety disorder with early onset: evidence of an intensity amplification bias

Abstract: The present event-related potential (ERP) study investigated for the first time whether children with early-onset social anxiety disorder (SAD) process affective facial expressions of varying intensities differently than non-anxious controls. Participants were 15 SAD patients and 15 nonanxious controls (mean age of 9 years). They were presented with schematic faces displaying anger and happiness at four intensity levels (25%, 50%, 75%, and 100%), as well as with neutral faces. ERPs in early and later time wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…To date, however, only a handful of ERP studies have examined emotional reactivity specifically in children with SAD. No differences have been reported between children with SAD and healthy controls via early ERP reactivity in response to emotional faces [16][17][18]. However, a recent study found enhanced P100 and N170 in children with mixed anxiety disorders (including SAD; [19]).…”
Section: Emotional Reactivity and Regulation In Childhood Sadmentioning
confidence: 94%
See 3 more Smart Citations
“…To date, however, only a handful of ERP studies have examined emotional reactivity specifically in children with SAD. No differences have been reported between children with SAD and healthy controls via early ERP reactivity in response to emotional faces [16][17][18]. However, a recent study found enhanced P100 and N170 in children with mixed anxiety disorders (including SAD; [19]).…”
Section: Emotional Reactivity and Regulation In Childhood Sadmentioning
confidence: 94%
“…It is also the first study to compare the responses of children with SAD to healthy and clinical control populations (children with mixed anxiety disorders (MAD)). First, we hypothesized that children with SAD would show heightened subjective and late ERP reactivity (LPP; [17,18,20]) in response to angry faces with socially threatening interpretations, but no differences in early ERPs (P100, N1700, EPN; [16][17][18]) when compared to HC children. Second, based on previous findings reporting reappraisal difficulties in adult SAD [6], we hypothesized that, compared to HC children, children with SAD would show smaller reappraisal effects on subjective and LPP responses (i.e.…”
Section: Limitations Of Previous Research and The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…FC estimation is mostly dependent on the use of the resting-state fMRI data of different brain sites. The level of FC is usually quantified between all neural activity units in the brain, irrespective of Luck, 2012Peelen et al, 2007Kolassa et al, 2009Kolassa et al, 2007Torrence et al, 2019Hagemann et al, 2016de Bruijn et al, 2020Meynadasy et al, 2019Fang et al, 2019 Peschard et al, 2013Luck, 2012Normann et al, 2007Kolassa et al, 2009Hagemann et al, 2016MacNamara et al, 2019 Xing et al, 2017Yuan et al, 2016Bhaumik et al, 2017Imperatori et al, 2019Prater et al, 2013Qiu et al, 2011Hahn et al, 2011Etkin and Wager, 2007Phan et al, 2006Kawaguchi et al, 2016Klumpp et al, 2012 GSAD patients display high decreased connection in the amygdala compared with baseline after application of CBT. Unanimity links used to differentiate SAD subjects are broadly located within or through the DMN Lower beta FC is shown in the right and the right amygdala and anterior cortex HSA displayed decreased FC between the amygdala and cortex compared to HC while watching fearful faces.…”
Section: Functional Connectivitymentioning
confidence: 99%